A parapsicologia é ciência? - Queiroz, Fábio Lázaro Oliveira (2022)
The purpose of this work is to investigate the scientificity of a questioned area: parapsychology. Accordingly, in the first chapter it is presented the current and historical context of what came to be known as “the demarcation problem”, i.e., the task of characterizing and demarcating science from non-science and, specifically, pseudoscience. In chapter two, it is presented a current demarcation criterion that is considered adequate for the demarcation task at hand. In the third chapter, some incursions are made in the historical record of the demarcation problem as it concerns parapsychology. Only in the fourth chapter it is presented the case-study itself. Its main focus is to present the debate regarding the scientificity of parapsychology. With that in mind, it is intended at the same time to deepen the understanding of the demarcation problem and to contribute to the practical task of demarcating areas which have its scientific status disputed. In this and in the final chapter, it is argued in favor of the scientific status of parapsychology, showing how the commonly alleged reasons against it fail to cast the area as a pseudoscience. Finally, in the final remarks it’s briefly resumed the themes of the previous chapters in an attempt to provide a general view of the path taken in this thesis, where it is reinforced the criticism of aspects of the demarcation criterion employed in regard to its philosophical commitments, like the mind-body monism, as well as the special care that must be taken when demarcating polemical disciplines in virtue of certain groups’ commitments to a distorted image of the sciences, which is in turn deployed to defend the sciences as they understand them.